2010
DOI: 10.5694/j.1326-5377.2010.tb03475.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and fatal drug overdose in child sexual abuse victims: a historical cohort study

Abstract: Objective: To determine the rate and risk of suicide and accidental fatal drug overdose (ie, overdose deemed not to have been suicide) in individuals who had been medically ascertained as having been sexually abused during childhood. Design: A historical cohort linkage study of suicide and accidental drug‐induced death among victims of child sexual abuse (CSA). Setting and patients: Forensic medical records of 2759 victims of CSA who were assessed between 1964 and 1995 were obtained from the Victorian Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 18 publications
(18 reference statements)
6
49
0
1
Order By: Relevance
“…Of note, another study of opiate users found that a history of sexual and/or physical abuse was associated with non-fatal overdose in participants who had also attempted suicide (Maloney, Degenhardt, Darke, & Nelson, 2009). Our finding regarding sexual abuse is particularly alarming given evidence that people who have experienced childhood sexual abuse are considerably more likely to die of overdose, compared to those without a history of sexual abuse (Cutajar et al, 2010). …”
Section: Discussionmentioning
confidence: 79%
“…Of note, another study of opiate users found that a history of sexual and/or physical abuse was associated with non-fatal overdose in participants who had also attempted suicide (Maloney, Degenhardt, Darke, & Nelson, 2009). Our finding regarding sexual abuse is particularly alarming given evidence that people who have experienced childhood sexual abuse are considerably more likely to die of overdose, compared to those without a history of sexual abuse (Cutajar et al, 2010). …”
Section: Discussionmentioning
confidence: 79%
“…The current evidence suggests that in comparison to the rates of suicides in the general population, children and adolescents suffering from PTSD or depression and especially from PTSD associated with co-morbid depression demonstrate higher rates of suicides [4,49-52]. The model includes age-related probabilities of suicide for each of the following health states: the PTSD + depression, PTSD only and Depression only to capture the long-term consequences of mental health interventions in terms of reduced rates of suicide.…”
Section: Methodsmentioning
confidence: 99%
“…Suicide rates associated with other mental health conditions (Markov states "PTSD + depression", "PTSD only" and "Depression only") were obtained from the published literature [4,49-51]. …”
Section: Methodsmentioning
confidence: 99%
“…Weich's 2009 review of cohort studies found only two with appropriate data; they found strong associations with suicidal ideation and attempts. The Victoria study data particularly high-lighted the high rates of suicide and accidental (presumed) fatal drug overdose [295]. A related phenomenon - self injurious behaviour has also been linked to child abuse in two reviews from 2008 and 2009 [296, 297], though in the latter case, the authors had little confidence in respect of child sexual abuse.…”
Section: Section B Childhood Factors and Evidence For Their Impact Omentioning
confidence: 99%